Observation of Transient Luminous Events (TLEs) In Pekan - Chan, Hwee Geem; M. S., Jadin; Amir Izzani, Mohamed (2015)
Transient Luminous Events (TLEs) are classified as a type of lightning events that occurs above a thunderstorm. It is a very fast event that is hardly seen by the naked eyes and happened in a very short period of time. So, a high frame rate capturing device is required in order to capture the scenes of TLEs. This paper reveals a study to verify the occurrences possibility of TLEs in Malaysia by selecting a simple and suitable device to detect and capture the event. There are various types of TLEs such as Elves, Sprites, Halos, Blue Jets, and Gigantic Jets that differs in height within atmosphere. Experimental studies are made to observe Elves and Sprites in Malaysia partially in Pekan, Pahang. The event is being traced using amplified antenna with noise filter and a data acquisition (DAQ) module used to interface between antennas and personal computer (PC) aided with online data logging device to perform a live characteristic recording through PC software. Verification of the obtained TLEs data will be carried out by comparing them with data recorded by Department of Meteorology Malaysia.